Implementasi Nilai Pendidikan Karakter dalam Pembelajaran Pendidikan Pancasila Kelas V di Madrasah Ibtidaiyah Negeri 6 Demak - Siti Dewi Rahmawati; Rakanita Dyah Ayu Kinesti (Lembaga Yasin AlSys, 2025)
The advancement of globalization has had adverse effects on student character, making character education a critical component to be integrated into learning, particularly at the elementary level. This study aims to describe the implementation of character education values in the teaching of Pancasila Education in Grade V at MIN 6 Demak, and to identify the strategies employed by teachers. A qualitative descriptive method was used, with data collected through observation, interviews, and documentation. The research was conducted in Grade V of MIN 6 Demak, focusing on the planning, implementation, and evaluation stages of instruction. The findings indicate that character values were effectively implemented throughout the stages of learning, including the introduction, core activities, and conclusion. Teachers applied various strategies to instill religious and national values, such as integrating character values into teaching materials, encouraging positive behavior, modeling exemplary conduct, regularly conducting flag ceremonies, and collaborating with parents. The study concludes that Pancasila Education at MIN 6 Demak serves as a strategic vehicle for systematically and comprehensively instilling student character. The findings underscore the importance of collaboration among teachers, schools, parents, and students in cultivating strong and sustainable character from an early age.